Development of Interactive E-LKPD Assisted by Liveworksheets in Science Learning for Grade IV Elementary Schools: Pengembangan E-LKPD Interaktif Berbantuan Liveworksheets Pada Pembelajaran IPAS Kelas IV Sekolah Dasar - Vivi Maidila; Raimon Efendi; Gunawan Ali (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2026)
This research is motivated by the real field issues of low motivation and learning outcomes among Grade IV elementary school students in Science and Social Studies (IPAS), particularly on the topic 'Forces Around Us'. Conventional learning media such as printed textbooks and black-and-white worksheets tend to be monotonic and fail to facilitate contextual learning needs based on the Independent Curriculum. This Research and Development (R&D) study using the 4D model (Define, Design, Develop, Disseminate) aims to produce an interactive Electronic Student Worksheet (E-LKPD) based on the Problem-Based Learning (PBL) model using Canva and the Liveworksheets platform that is valid, practical, and effective. The results demonstrated that the validation scores achieved 93.75% for language (Very Valid), 78.00% for content/material (Valid), 85.00% for graphics (Very Valid), 86.00% for the teaching module (Very Valid), and 86.00% for test items (Very Valid). The practicality score from the teacher reached 97.3%, and students' responses ranged between 95% and 100% (Very Practical). The effectiveness test proved a significant improvement in learning outcomes, reaching a classical mastery rate of 92.31% in the main field trial and 90.90% in the dissemination phase. In conclusion, the developed interactive E-LKPD based on PBL using Liveworksheets is highly feasible, practical, and effective as an innovative learning medium in elementary schools.